The muslim researcher reflections of insider/outsider research in Indonesia = Peniliti muslim refleksi penilitian insider dan outsider di Indonesia - Seise, Claudia (Azizah) (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
he article takes up the topic of religious insider and outsider research and looks especially at the issue of advantages and disadvantages of being a religious insider doing qualitative research in religious communities similar to one’s own. As a case study serves my personal experience of being a convert Muslim woman doing research among Islamic communities in Indonesia. During research, I came to understand that the plurality of different Islamic practices found in Indonesia makes it difficult to become a ’true’ and ‘complete‘ insider to this variety of Islamic teachings and practices. My main argument is that, at least in the Indonesian context, it is impossible to be a complete religious insider to each aspect of the plurality of Islamic practices despite being an insider to Islam, a Muslim. This in turn leads me to discuss advantages and disadvanatges of being a religious insider.